HUBUNGAN AKTIFITAS FISIK DENGAN STATUS GIZI SISWA MADRASAH IBTIDAIYAH NURUSSALAM - Damayanti, Amilia Yuni; Darni, Joyeti; Octavia, Ruskiah (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
AbstractBackground: Nutritional status can be affected by physical activity. Physical activity aims to balance the energy intake and energy expenditure in the body. This cross-sectional study was conducted to assess the possible association between nutritional status and physical activities among school-aged children. Methods: School-aged children 10 and 12 years were selected from Islamic Primary School in Ngawi. Anthropometric measurements were taken using digital scales for weight and microtoise for height. The nutritional status was calculated using the standard of Z-Score. Physical activity was measured using questionnaire. Statistical test used Chi-square test. Results: We found that 83.9% participants of the study sample were classified as normal nutritional status and 16.1% were overweight.56.4% of respondents who are classified as normal weight have physical activity above the average (≥2.89), while respondents are classified as overweight having more physical activity above the average of 33.3%. Conclusion: There was no significantly difference between physical activities with nutritional status of school children (p= 0.071). Keywords:nutritional status, physical activities, school children. AbstrakLatar Belakang: Status gizi salah satunya dapat dipengaruhi oleh aktifitas fisik. Aktivitas fisik bertujuan untuk menyeimbangkan asupan energy dan pengeluaran energi dalam tubuh.Penelitian ini bertujuan untuk menganalisis hubungan antara aktifitas fisik dengan status gizi anak sekolah.Metode: Anak Usia Sekolah 10 hingga 12 tahun dipilih dari Sekolah Dasar Islam. Pengukuran antropometri dilakukan dengan menggunakan timbangan digital untuk mengukur berat badan dan microtoise untuk tinggi badan.Status gizi dihitung menggunakan standar Z-Score.Aktivitas fisik diukur menggunakan kuesioner.Uji statistik menggunakan uji Chi-square.Hasil: Sebesar 83.9% responden penelitian memiliki status gizi normal dan 16.1% tergolong gizi lebih. Sebanyak 56.4% responden yang tergolong status gizi normal memiliki aktivitas fisik di atas rata-rata (≥2.89), sedangkan responden tergolong memiliki status gizi lebih memiliki aktivitas fisik di atas rata-rata sebesar 33,3%. Kesimpulan: Tidak ditemukan adanya hubungan yang signifikan antara aktifitas fisik dnegan status gizi anak sekolah (p=0.071). Kata kunci: status gizi, aktifitas fisik, anak sekolah